2005
DOI: 10.1109/tns.2005.846872
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of gamma radiation effects on ultra-low input bias current linear circuits under biased conditions

Abstract: Abstract-Ultra-low input bias current linear circuits are used in several applications requiring them to work under varying conditions of temperature, humidity, radiation etc. which influence their performance. This paper presents a first time study of gamma radiation effects on ultra low input bias current linear circuits under biased conditions for small signal dc applications. Under biased conditions, radiation-induced photo currents play a significant role. A noncatastrophic radiation leakage environment h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It has been observed that the input bias current, input offset voltage, and input offset current of very low input bias current op-amps change significantly on exposure to gamma radiation. The input bias current of op-amps DN8500A, OPA111AM and INA101AM varies drastically [5], [9] with exposure to gamma radiation. The input bias current of the op-amp DN8500A increases from 0.023 pA to 0.145 pA after exposing to 5 krads.…”
Section: Simulation Of Icamentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that the input bias current, input offset voltage, and input offset current of very low input bias current op-amps change significantly on exposure to gamma radiation. The input bias current of op-amps DN8500A, OPA111AM and INA101AM varies drastically [5], [9] with exposure to gamma radiation. The input bias current of the op-amp DN8500A increases from 0.023 pA to 0.145 pA after exposing to 5 krads.…”
Section: Simulation Of Icamentioning
confidence: 99%
“…However, as mentioned earlier, the ion chamber bin is located adjacent to the reactor core for sensing neutron flux responsible for producing reactor power. A small fraction of the gamma radiation is able to leak out and may affect the semiconductor devices of the neighboring electronic systems, which are sensitive to gamma radiation exposure [6]- [9]. For example, it is well known that the basic parameters of an op-amp, e.g., the input bias current, the input offset voltage and the input offset current, change in the nuclear radiation environment [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The re sponse of volt age reg u la tors in the ra di ation en vi ron ment has been in ten sively ex am ined in previ ous years, pri mar ily due to their ad van tages over switch ing reg u la tors: a sim ple elec tric cir cuit, low price, re duced noise and rapid tran sient re sponse to load con di tions [1]. Con cern over the ex am i na tion of voltage reg u la tors par tic u larly arose af ter the dis cov ery of the en hanced low dose rate sen si tiv ity (ELDRS) ef fect, lead ing to the anal y sis of nu mer ous pro ce dures an tic ipated for the pro cure ment of pre cise in for ma tion on the ra di a tion tol er ance of sam ples de signed for ser vice on sat el lites in the space ra di a tion en vi ron ment [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%